Diego Armando Maradona: Globalization’s First Sports Superstar - Gupta, Amit (Funes. Journal of narratives and social sciences, 2022)
Maradona is important because he was the first superstar of an increasingly globalized world and in retirement his reputation only grew as we were able to follow the life and tribulations of the great man in real time—something that was not possible in a pre-globalized era. This paper examines the link between globalization and the status of Maradona as a global icon and argues that a combination of talent, a globally integrated economy, and a public persona that was larger than life, made Maradona the international star he was. This is in contrast to the overwhelming majority of sportsmen and women who lose their public prominence after retirement.